World economy lacks momentum - Günter Großer; Günter Weinert (Intereconomics, 1987)
After the price of oil began falling sharply during the first few months of 1986 the prospects for a more pronounced and long-lasting economic upswing in the industrialised countries were generally regarded as having improved. The increase in demand and production in 1986, however, was more restrained than expected. Against this background, what are the prospects for expansionary forces in 1987?
Keywords: 330; Economic Trends